The Waitangi Tribunal’s WAI 2575 Report - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Timothy (Health and Human Rights, 2020)
Te Tiriti o Waitangi, a treaty negotiated between Māori (the Indigenous peoples of Aotearoa) and the British Crown, affirmed Māori sovereignty and guaranteed the protection of hauora (health). The Waitangi Tribunal, established in 1975 to investigate alleged breaches of the agreement, released a major report in 2019 (registered as WAI 2575) about breaches of te Tiriti within the health sector in relation to primary care, legislation, and health policy. This article explores the implications of this report for the New Zealand health sector and the decolonial transformation of health systems. The tribunal found that the Crown has systematically contravened obligations under te Tiriti across the health sector. We complement the tribunal’s findings, through critical analysis, to make five substantive recommendations: (1) the adoption of Tiriti-compliant legislation and policy; (2) recognition of extant Māori political authority (tino rangatiratanga); (3) strengthening of accountability mechanisms; (4) investment in Māori health; and (5) embedding equity and anti-racism within the health sector. These recommendations are critical for upholding te Tiriti obligations. We see these requirements as making significant contributions to decolonizing health systems and policy in Aotearoa and thereby contributing to aspirations for health equity as a transformative concept.

Māori News is Bad News : That's certainly so on television - Moewaka Barnes, Helen; Nairn, Ray; Borell, Belinda; Gregory, Amanda; McCREANOR, TIMOTHY (MAI Journal, 2012)
A television news bulletin tells us, in effect, what we should think about and the preferred way in which we should think about it. Analyses of New Zealand media have consistently shown that news about Māori is both relatively rare and that it prioritises violence and criminality. Researchers conclude this encourages New Zealanders to see Māori as threatening the social order and burdening our society. We examined the few Māori stories broadcast in a large representative sample of English-language television news bulletins and found the same negativity. As our sample included Māori-language news bulletins from the same days we know there were other Māori news stories available, so we conclude that the prioritising of negative stories about Māori in English-language media is a matter of choice. Focus groups with Māori and non-Māori media consumers demonstrate the impact of the relentlessly negative portrayals of Māori in New Zealand media.

Media & Te Tiriti o Waitangi 2004 - Moewaka Barnes, Angela; Gregory, Mandi; McCreanor, Timothy; Nairn, Raymond; Pega, Frank; Rankine, Jenny (Kupu Taea, Media and Te Tiriti Project, 2005)
Keywords: iwi taketake; journalism; mass media and race relations; media; tiriti o waitangi/treaty of waitangi

Media & te Tiriti o Waitangi 2007 - Rankine, Jenny; Nairn, Raymond; Moewaka Barnes, Helen; Gregory, Mandi; Kaiwai, Hector; McCreanor, Timothy (Kupu Taea, Media and Te Tiriti Project, 2007)
Keywords: iwi taketake; journalism; kōrero; mass media and race relations; media; rangahau māori; tiriti o waitangi/treaty of waitangi

The Association of Crime Stories and Maori in Aotearoa New Zealand Print Media - McCreanor, Timothy; Rankine, Jenny; Moewaka Barnes, Angela; Borell, Belinda; Nairn, Raymond; McManus, Anna-Lyse (Sites: A Journal of Social Anthropology and Cultural Studies, 2014)
This paper explores associations between crime reporting and Maori ethnicity in a large representative sample of newspaper items gathered in Aotearoa New Zealand between November 2007 and April 2008, using content, thematic and discursive analyses and audience interpretations. The association of Maori and crime was prominent in these newspapers and Maori were frequently labelled as possible or actual perpetrators of crime on superficial judgements, often by victims. This practice associates Maori with all accounts of crime and embeds crime as a background for all other items about Maori. In contrast, newspaper coverage of Pakeha perpetrators of a crime against a Maori organisation worked to valorise the convicted thieves. This embedding of crime as a background to other stories about Maori, the pervasive but unacknowledged Pakeha1 norms, and media positioning of Maori as a threat in non-crime stories, is central to hegemonic discourses of Maori-Pakeha relations. Focus groups participants indicated that these discourses support real-world marginalisation and discrimination against Maori in Aotearoa New Zealand.
Keywords: crime; news media; racism